2008
DOI: 10.1097/mlg.0b013e31816dd2e9
|View full text |Cite
|
Sign up to set email alerts
|

Free Abdominal Fat Transfer for Reconstruction of the Total Parotidectomy Defect

Abstract: FAT reconstruction of the total parotidectomy defect is associated with greater blood loss from the FAT donor site and increased surgical time, but is safe and highly effective. These data suggest that the benefits of FAT reconstruction outweigh the additional increment in operative time and blood loss observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 11 publications
3
64
0
2
Order By: Relevance
“…It adds approximately 15 to 30 minutes of operative time, causes minimal additional blood loss, and does not lengthen hospital stay. 15,18 In the present study, sub-umbilical fat harvesting was simple, effective and without complications, and was utilised in all cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It adds approximately 15 to 30 minutes of operative time, causes minimal additional blood loss, and does not lengthen hospital stay. 15,18 In the present study, sub-umbilical fat harvesting was simple, effective and without complications, and was utilised in all cases.…”
Section: Discussionmentioning
confidence: 98%
“…27 Abdominal free fat grafts have previously been used successfully in parotid surgery. 15,17,18 Fat is a favourable graft material following parotidectomy as it has a similar texture and consistency to parotid tissue. It is readily accessible, with multiple potential donor sites that leave minimal, well hidden incision scars.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that the average duration of drainage in uncomplicated head and neck operations is between 2-4 days. [7][8][9][10] The presence of drains may in fact encourage further drainage by stimulating tissue reactions or by creating a suction effect.…”
Section: Discussionmentioning
confidence: 99%
“…The deformity resulting from these ablative procedures are a significant source of cosmetic morbidity and postoperative dissatisfaction 1 . In order to maximize the ultimate cosmetic and functional outcome for an individual wound, the head and neck surgeon must possess a firm grasp of fundamental techniques, as well as the ability to use a reconstructive modality that meets the unique demands of each defect after a thorough defect analysis.…”
Section: Discussionmentioning
confidence: 99%